Peraturan Daerah dan Penegakan Legalitas Pengendalian Kapal Ilegal dalam Mendukung Investasi Pariwisata di Labuan Bajo - Cheryl Nathania; Dinda Aurelia Rosi Nasution; Keisha Zahra Wibowo; Nicole Eugenia Yuri; Najla Azrijal Chosaf (Journal of Legal, Political, and Humanistic Inquiry, 2026)
This study analyzes the role of local regulations in enforcing the legality of controls on illegal vessels to support tourism investment in Labuan Bajo as a national super-priority destination. The legal issues examined focus on the lack of harmonization between central and local regulations, weak law enforcement against unlicensed vessels, and the implications for legal certainty and the investment climate. The research method employed is a normative legal approach using legislative, conceptual, and comparative methodologies, through an analysis of Law No. 17 of 2008 on Shipping, Government Regulations, Presidential Regulations, Ministerial Regulations, and relevant court decisions. The research findings indicate that Regional Regulations serve a strategic function as an instrument for harmonizing standards and strengthening oversight of tourist vessel activities. Effective law enforcement against illegal vessels has been shown to contribute to improved maritime safety, tourist protection, and legal certainty for investors. Challenges such as overlapping jurisdictions and weak inter-agency coordination still persist. The theoretical implications of this study underscore the importance of integrating maritime and tourism laws within a sustainable development framework. Therefore, an adaptive, legality-based, and integrated reformulation of local policies is necessary to enhance the appeal of tourism investment in Labuan Bajo.